2006
DOI: 10.1136/jcp.2004.025452
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of G(-174)C IL-6 polymorphism and plasma concentrations of inflammatory markers in patients with type 2 diabetes and peripheral arterial disease

Abstract: Aims:To determine whether the G(−174)C interleukin 6 (IL-6) polymorphism influences the development of peripheral arterial disease (PAD) in individuals with type 2 diabetes. This was investigated by comparing the distribution of G(−174)C genotypes between patients with type 2 diabetes and PAD (PAD+) and those with type 2 diabetes but without PAD (PAD−). Plasma concentrations of IL-6, fibrinogen, C reactive protein (CRP), and vascular endothelial growth factor (VEGF) were also compared in PAD+and PAD−patients.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 32 publications
2
51
1
2
Order By: Relevance
“…Thus, we hypothesize that N is useful in identifying the activated process of macrophage cells in patients with chronic PAD. It is known that different biomarkers of inflammation, such as interleukins or metalloproteinases are elevated both in chronic and more severe PAD patients (32)(33)(34)(35)(36)(37)(38). Results of this study have shown the involvement of activated macrophages in chronic arterial disease of the lower limbs, albeit not symptomatic.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, we hypothesize that N is useful in identifying the activated process of macrophage cells in patients with chronic PAD. It is known that different biomarkers of inflammation, such as interleukins or metalloproteinases are elevated both in chronic and more severe PAD patients (32)(33)(34)(35)(36)(37)(38). Results of this study have shown the involvement of activated macrophages in chronic arterial disease of the lower limbs, albeit not symptomatic.…”
Section: Discussionmentioning
confidence: 55%
“…The G-174C IL-6 polymorphism had been documented to increase the development of PAD 41,42) and incidence of CVD [43][44][45] . The risk GG genotype of IL-6 can increase IL-6 release 41,42) , which in turn increases the release of fibrinogen and CRP 42) . From the Framingham Offspring Study 37) , increased serum IL-6 and TNF receptor 2 (TNFR2) levels were associated with ABI decline and clinical PAD (intermittent claudication).…”
Section: Discussionmentioning
confidence: 99%
“…They found significantly lower VEGF expression in patients suffering from type 2 diabetes in comparison with the control group and emphasized the involvement of other above-mentioned factors in angiogenesis. Libra et al (2006) analyzed the impact of genetic polymorphism on interleukin-6 (IL-6) which affects VEGF secretion. Specific IL-6 genotypes were identified in individuals with type 2 diabetes coexistent with PAD, which induced higher VEGF levels in diabetic patients with PAD.…”
Section: Discussionmentioning
confidence: 99%